Handgrip Strength as an Indicator of Quality of Life in Chronic Kidney Disease Patients Undergoing Hemodialysis - Tiara Amalia; Christina J.R Esmaralda Lumbantobing; Linda Chiuman; Samuel Joshua Hamonangan Tua Rajagukguk (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2025)
Handgrip strength has been associated with various chronic diseases, length of hospitalization, cognitive decline, and even mortality. Hemodialysis administered to patients with chronic kidney disease affects their physical functioning, manifested as fatigue, mobility limitations, and a decline in the ability to perform daily activities. The goal of this study was to look at how hemodialysis patients at Rasyida Kidney Specialty Hospital Medan felt about their quality of life in relation to their grip strength. The research team used a cross-sectional analytical observational design to compile their findings. At Rasyida renal Hospital Medan, 52 patients with chronic renal disease who were receiving hemodialysis were included in the study. All participants had to meet the inclusion and exclusion criteria that were previously established. The research team used a handgrip dynamometer to measure grip strength, and the WHOQOL-BREF to assess quality of life. Processing of the data involved both bivariate and univariate analyses. Findings: There was a statistically significant correlation between age (p = 0.001) and both sex and quality of life (p = 0.003). Nevertheless, neither handgrip strength (p = 0.156), comorbidities (p = 0.618), nor the length of time on hemodialysis (p = 0.746) were significantly associated with quality of life. Conclusion: Physical strength as measured by handgrip, comorbid diabetes mellitus, and length of dialysis treatment do not seem to have a significant impact on quality of life among hemodialysis patients with chronic kidney disease. However, demographic characteristics, such as age and sex, do affect quality of life. Physical capacity as measured by handgrip strength is less important than demographic determinants in determining quality of life, according to these studies. Therefore, interventions aimed at improving quality of life are required, including social support and a care approach that focuses particularly on elderly patient groups rather than solely on physical aspects